حوار الحضارات من منظور الثقافة الهندية - نجار, نوال (كلية الأدب العربي والفنون, 2024)
لترجمة الأدب دورٌ كبير في تحقيق الإنفتاح و استيعاب التّنوع الثَّقافي والحوار الحضاري الأدبي بين الأمم . ولا يخفى على دارس الأدب العربي قَديمه وحديثه ما لهذا الحوار من قيمٍ متعددّة الفائدة . حوارٌ بدأ مع الذّات والغير والآخر ليستقطِبَ القَول ويعيد صياغته ويُرسِلَه مغمّساً بوجدان الغير والآخرين . من أهمّ القنوات التي كان من شأنها مدّ جسور الحوار الحضاري الأدبي الأساطير والقصص الشّعبيّة الهندية القديمة ، حيث شكّلت هذه الأخيرة لبِنةً بارزة في صرحِ التّأثير الأدبي والثّقافي على الشّعوب حاملةً في طيّاتها أشكالاً من الحِكمة والأخلاق الفاضِلة . ولقد حمِلت الأسطورة التي إخترناها أنموذجا لهذه الدّراسة التّاريخية التّحليليّة الوصفيّة الفنّية المقارناتيّة، مجموعةً من القصص والحكم التي تصوّرُ بوضوحٍ ثنائيّة إخفاءِ المعرفة وكشفِها وتُشعِلُ شرارة التأويل عندَ القارئ. وقد تعدّدَت أوجهُ تلقّي قصة "بلوهر ويوذاسف" وتمّت إعادة تأويلها عبر العصور .ويتّفِق إستعمال قصص الأمثال بشَكلٍ وفير في هذه الأسطورة مع الشُّهرة الواسعة التي حَظِيت بها والإنتشار العابر للحضارات .حيث ساهَمت إلى حدّ ما في عمليّة التّحاور الحضاري بمفاهيمها الإنسانيّة التي انتقَلت بين اللّغات والآداب المختلفة ، وهي تصنّف من القصص الصّوفيّة الأخلاقيّة . وجاءت هذه الدّراسة معنونة بـــ : " حوار الحضارات من منظور الثّقافة الهنديّة ــ قصّة بلوهر ويوذاسف ـــ أنموذجاً ، محاولةً رصد التّجاذبات والتّقاطعات بين ما قدّمهُ كل من الهنود والعَرب لبعضهم البعض . وتقصي مختلف القيم الإنسانيّة المشتركة بين الحضارتين . كما يُقارب هذا البحث الإجابة عن إشكاليَّة عامَّة وهي : هل تعتبر قصّة بلوهر وبوذاسيف وجهاً من أوجه التّقارب الحضاري بين العرب المسلمين و الهنود؟ وهل نجح هذا الكتاب في تقديم قصصه وفق سردٍ تعليمي تربويّ إنسانيّ متكامل له خصوصيته الحضارية الإسلاميّة الهنديّة؟ Translation of literature has played a major role in achieving openness and assimilation of cultural diversity and literary civilizational dialogue between nations. It is no secret to the student of Arabic literature, ancient and modern, that this dialogue has many beneficial values. A dialogue that began with the self, others, and the other to attract the statement, reformulate it, and send it immersed in the feelings of others and others. One of the most important channels that would have built bridges of literary civilizational dialogue were ancient Indian myths and folk stories, as the latter formed a prominent building block in the edifice of literary and cultural influence on peoples, carrying within them forms of wisdom and virtuous morals. The myth that we chose as a model for this historical, analytical, descriptive, and artistic study contains a set of stories and sayings that clearly depict the duality of concealing and revealing knowledge and ignite the spark of interpretation in the reader. The story of “Bluhar and Budhasaph” has been received in many ways and has been reinterpreted throughout the ages. The abundant use of proverbial stories in this legend is consistent with the wide fame it enjoyed and its spread across civilizations. It contributed to some extent to the process of civilizational dialogue with its human concepts that were transferred between languages and literatures. Various, and it is classified as a Sufi moral story. This study is entitled: "Dialogue of Civilizations from the Perspective of Indian Culture - The Story of Balur and Bodhisattva - as a Model", an attempt to monitor the tensions and intersections between what the Indians and Arabs have presented to each other. And to investigate the various human values shared by the two civilizations. This research approaches the answer to a general problem, which is: Is the story of Balur and Bodhisattva considered an aspect of the cultural convergence between Arab Muslims and Indians? And has this book succeeded in presenting its stories according to an educational narrative that is integrated with its own Islamic-Indian cultural specificity?
قصة بلوهر و يوذاسف أنموذجا
Keywords: الحوار الحضاري ـ التّرجمة ـ القصص الشّعبيّة ــ الفِكر الإنساني; Civilizational dialogue - translation - folk stories - human thought.